Analysis of Monthly Rainfall Characteristics in Nusa Tenggara Timur and its Spatial and Temporal Shifts - Afghani, Fadhli Aslama; Ofana Tri Wibowo; Imawan Mashuri; Zuhairul A, Hasyid Agha (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
The spatial characteristics of rainfall in Nusa Tenggara Timu for the periods 1961-1990 and 1991-2020 show similarities in terms of topography influencing local variations in rainfall intensity. Additionally, inland areas and the northern side of region experience higher rainfall compared to the coastal areas and the southern side. On the other hand, temporal characteristics reveal a monsoonal rainfall pattern with peak precipitation occurring in January and the lowest rainfall in August. Furthermore, there is a normal shift in rainfall patterns between the two periods, marked by a reduction in the intensity of dark colors in the 1991-2020 period compared to 1961-1990. There is also a positive shift in normal rainfall values for the months of April and December, while the remaining months experience a negative shift.